Consumer behavior and marketing strategy - Peter, J. Paul. (Irwin, 1996)
Introduction to consumer behavior and marketing strategy. A framework for consumer analysis. Introduction to affect and cognition. Consumers' product knowledge and involvement. Attention and comprehension. Attitudes and intentions. Consumer decision making. Introduction to behavior. Classical and operant conditioning. Vicarious learning. Analyzing consumer behavior...